POTENTIAL CYTOTOXIC DRUG EFFECTS OF SECONDARY METABOLITES DERIVED FROM SELECTED MEDICINAL PLANTS OF SAVANADURGA FOREST IN KARNATAKA - Ravikumar, Ashwatha Reddy; Madgaonkar, Varun; VENKATESHA, R. T.; R., BHARATHI; Murthy, V. Krishna (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: To evaluate the potential cytotoxic and antitumor activities of secondary metabolites of selected medicinal plants of Savanadurga forest, Karnataka. Methods: The soxhlet extracted crude methanolic leaf extracts of nineteen medicinal plants were assessed for their potential cytotoxic and antitumor activities by brine shrimp lethality assay and potato tumor inhibition assay at 100Î¼g/ml respectively. Results: Kirganelia reticulata and Cissus quadrangularis showed highest cytotoxicity while Flacourtia indica failed to show any inhibitory activity in brine shrimp lethality assay. Kirganelia reticulata exhibited 100% antitumor activity while Albizzia amara failed to show any antitumor activity as tested by crown gall tumor inhibition assay. Conclusion: Both brine shrimp lethality assay and potato tumor inhibition assay indicated that Kirganelia reticulata seems to be the best anticancer plant.